A history of Scottish philosophy - Broadie, Alexander (Edinburgh : Edinburgh University Press, 2009)
This book is unique in that it provides the first-ever substantial account of the seven-centuries-old Scottish philosophical tradition. The book focuses on a number of philosophers in the period from the later-thirteenth century until the mid-twentieth and attends especially to some brilliantly original texts.
John Duns Scotus -- The fifteenth century -- The circle of John Mair -- Humanism and after -- Scotland moves into the age of Enlightenment -- David Hume -- Adam Smith -- The Scottish school of common sense philosophy -- The nineteenth century : Ferrier to Seth -- Realism and idealism : some twentieth-century narratives.
Keywords: Philosophy, Scottish -- History; Philosophy, Scottish; Philosophy; filosofia; historia; Scotland -- History; Skotlanti